Organoleptic Test of Eco-enzyme : Fermentation of Banana Peel Waste - Juen Carla Warella (Universitas PGRI Semarang, 2023)
Prevention of environmental damage can be done by recycling household waste both organic and inorganic. One of them is by making eco-enzymes made from banana peel waste which is found in the environment. This study aims to determine the level of respondents' liking based on organoleptic test variables. This research method is an experiment that includes making eco-enzymes, and organoleptic tests consisting of aroma, color and texture variables. Data analysis was carried out in a qualitative descriptive way by looking at the level of respondents' liking. The results showed that the average respondent chose a brown color with a percentage of 90%, yellow 7%, and colorless 3%. The scent variable respondents chose sour odor by 70% and other aromas 30%. While the texture of all respondents chose the composition of liquid eco-enzyme. This is due to the metabolic activity of microorganisms that result in the breakdown of substrates by bacteria resulting in changes in the aroma, color and texture of banana peels. The conclusion of this study is that the use of banana peel as the basic ingredient for making eco-enzyme affects the respondents' level of liking. Eco-enzyme can be used as a natural fertilizer for plant growth and can reduce household waste.